A Home-Treatment Algorithm Based on Anti-inflammatory Drugs to Prevent Hospitalization of Patients With Early COVID-19: A Matched-Cohort Study (COVER 2) - Consolaro, Elena; Suter, Fredy; Rubis, Nadia; Pedroni, Stefania; Moroni, Chiara; Pastò, Elena; Paganini, Maria Vittoria; Pravettoni, Grazia; Cantarelli, Umberto; Perico, Norberto; Perna, Annalisa; Peracchi, Tobia; et al. (Frontiers in Medicine, 2022)
Background and Aim: While considerable success has been achieved in the management of patients hospitalised with severe coronavirus disease 2019 (COVID-19), far less progress has been made with early outpatient treatment. We assessed whether the implementation of a home treatment algorithm – designed based on a pathophysiologic and pharmacologic rationale – and including non-steroidal anti-inflammatory drugs, especially relatively selective cyclooxygenase-2 inhibitors and, when needed, corticosteroids, anticoagulants, oxygen therapy and antibiotics – at the very onset of mild COVID-19 symptoms could effectively reduce hospital admissions. Methods: This fully academic, matched-cohort study evaluated outcomes in 108 consecutive consenting patients with mild COVID-19, managed at home by their family doctors between January 2021 and May 2021, according to the proposed treatment algorithm and in 108 age-, sex-, and comorbidities-matched patients on other therapeutic schedules (ClinicalTrials.gov: NCT04854824). The primary outcome was COVID-19-related hospitalisation. Analyses were by intention-to-treat. Results: One (0.9%) patient in the ‘recommended’ cohort and 12 (11.1%) in the ‘control’ cohort were admitted to hospital (P=0.0136). The proposed algorithm reduced the cumulative length of hospital stays by 85%, (from 141 to 19 days) as well as related costs (from €60.316 to €9.058). Only 9.8 patients needed to be treated with the recommended algorithm to prevent one hospitalisation event. The rate of resolution of major symptoms was numerically – but not significantly – higher in the ‘recommended’ than in the ‘control’ cohort (97.2% versus 93.5%, respectively; P=0.322). Other symptoms lingered in a smaller proportion of patients in the ‘recommended’ than in the ‘control’ cohort (20.4% versus 63.9%, respectively; P<0.001), and for a shorter period. Conclusion: The adoption of the proposed outpatient treatment algorithm during the early, mild phase of COVID-19 reduced the incidence of subsequent hospitalisation and related costs.